REFORMASI BIROKRASI DAN PERWUJUDAN GOOD GOVERNANCE DALAM PRESPEKTIF PELAYANAN PUBLIK (STUDI KANTOR CAMAT TENGGARONG) - Martain Martain (MAHAKAM: Jurnal Ilmu-Ilmu Sosial, 2015)
Some problem or weakness occur according to researchers at the district office Tenggarong, Still constraints and weaknesses of human resources; The lack of alacrity and the responsibility of public service officer; yet embedded trust of officers who provide services; lack of attention from the public service to access the communication, clear information, courtesy, friendliness to the recipients of public services; Well not yet well established in relation to environmental issues Tenggarong Head Office.the purpose of this study was to describe, identify and evaluate on the implementation of the Reforms and the embodiment of good governance in the public service perspective in Tenggarong Head Office.Key word: Reformasi Birokrasi, Pelayanan